1999
DOI: 10.1101/gad.13.2.163
|View full text |Cite
|
Sign up to set email alerts
|

Multiple docking sites on substrate proteins form a modular system that mediates recognition by ERK MAP kinase

Abstract: MAP kinases phosphorylate specific groups of substrate proteins. Here we show that the amino acid sequence FXFP is an evolutionarily conserved docking site that mediates ERK MAP kinase binding to substrates in multiple protein families. FXFP and the D box, a different docking site, form a modular recognition system, as they can function independently or in combination. FXFP is specific for ERK, whereas the D box mediates binding to ERK and JNK MAP kinase, suggesting that the partially overlapping substrate spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
481
3
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 449 publications
(507 citation statements)
references
References 37 publications
14
481
3
3
Order By: Relevance
“…The role of this motif in the MAP kinase phosphatases has yet to be established, although it has been suggested that it could serve as an interaction point with cell cycle proteins (Martell et al, 1998). Moreover, the MKP5 protein appears to contain another conserved motif known as the Dbox (Jacobs et al, 1999). Alignment of DNAbinding proteins containing such motifs has resulted in the following consensus:…”
Section: Identi®cation Of a Novel Human Dual-speci®city Phosphatasementioning
confidence: 99%
See 2 more Smart Citations
“…The role of this motif in the MAP kinase phosphatases has yet to be established, although it has been suggested that it could serve as an interaction point with cell cycle proteins (Martell et al, 1998). Moreover, the MKP5 protein appears to contain another conserved motif known as the Dbox (Jacobs et al, 1999). Alignment of DNAbinding proteins containing such motifs has resulted in the following consensus:…”
Section: Identi®cation Of a Novel Human Dual-speci®city Phosphatasementioning
confidence: 99%
“…This motif has been suggested to function as a docking site that mediates binding to ERK and JNK MAP kinases. The dual-speci®city phosphatase M3/6 (Theodosiou et al, 1996) also contains this consensus whereas MKP1/CL100 and MKP-2 (Keyse and Emslie, 1992; Misra-Press et al, 1995) contain a more highly conserved motif (FXFP) which is speci®c for mediating binding to ERK (Jacobs et al, 1999). Interestingly, in all the above cases, the MAPK docking motifs are located C-terminally to the catalytic domains of the phosphatases as compared to MKP5, where the motif is located Nterminally.…”
Section: Identi®cation Of a Novel Human Dual-speci®city Phosphatasementioning
confidence: 99%
See 1 more Smart Citation
“…of at least four independent experiments in duplicate PKA-phosphorylation-dependent (Zhong et al, 1998). Importantly, MAP kinases contact their substrates through speci®c docking sites (Jacobs et al, 1999), and compatible DEF and DEJL docking motifs are present both in the c-Rel DNA binding and transactivation domains.…”
Section: Discussionmentioning
confidence: 96%
“…A second docking motif (consensus L-X 1-2 -(R/K) [2][3][4][5] ), related to the D-site, is found in MAPK-activated kinases such as RSK1 [50]. Another docking motif for MAP kinases (consensus FXFP) has been named the 'DEF motif' [51]. Fig.…”
Section: Mapk-docking Sites On Substrates and Regulatorsmentioning
confidence: 99%